2019
DOI: 10.1016/j.quageo.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for distal transport of reworked Andean tephra: Extending the cryptotephra framework from the Austral volcanic zone

Abstract: Cryptotephra deposits (non-visible volcanic ash beds) may extend thousands of kilometres and provide valuable chronological isochrons. Here, we present a Lateglacial-early Holocene (c. 16,500 cal yr BP-6,000 cal yr BP) tephrostratigraphy from Hooker's Point, East Falkland, South Atlantic. This period spans the last glacial termination across the southern mid-latitudes, a time period during which the palaeoenvironmental record is poorly resolved in southern South America and the South Atlantic. The development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The methodology and results of cryptotephra (non-visible volcanic ash), pollen and plant macrofossil analyses from Hooker's Point, including volcanic-glass chemical compositions (Reclus Volcano R1 and Mt. Burney MB1), are presented by Monteath et al (2019) and Scaife et al (2019).…”
Section: Laboratory Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology and results of cryptotephra (non-visible volcanic ash), pollen and plant macrofossil analyses from Hooker's Point, including volcanic-glass chemical compositions (Reclus Volcano R1 and Mt. Burney MB1), are presented by Monteath et al (2019) and Scaife et al (2019).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Two 14 C dates were placed directly beneath cryptotephra deposits associated with the Reclus Volcano R1 and Mt. Burney MB1 volcanic eruptions in order to provide more precise age constraints for these regional isochrons (Monteath et al, 2019).…”
Section: Chronologymentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, pyroclastic flows tend to form un-sorted thick deposits (ignimbrites) up to distances ranging from few to tens of km from the vent [6][7][8][9][10]. Tephras, i.e., loose pyroclastic materials of any origin [9,11,12] and lithified tephras labelled here volcanic-rich layers (VRL), can be the unique witnesses of dismantled volcanoes, erased by tectonic or erosive processes [9,[13][14][15][16][17][18][19]. Finally, there are cryptotephras, i.e., sedimentary levels hosting volcanic materials [9,20].…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of cryptotephra deposits originating from Patagonian explosive volcanism have previously been reported in peat bogs across the Southern Atlantic, including the Falkland Islands and South Georgia (Hall et al, 2001;Oppedal et al, 2018), with the most recently identified linked to eruptions at Mt. Burney (MB1; 8.85-9.95 ka cal BP) and the Reclus Volcano (R1; 14.76 ± 0.18 ka cal BP (Monteath et al, 2019;Stern et al, 2011).…”
Section: Introductionmentioning
confidence: 99%